CABOZANTINIB-INDUCED SCROTAL ULCERATION IN A PATIENT WITH ADVANCED HEPATOCELLULAR CARCINOMA: A CASE REPORT - Kripa Mariyam John; Surabhi Soman; Harikrishnan Harikrishnan (World Journal of Biology Pharmacy and Health Sciences, 2026)
Cabozantinib is an oral multikinase inhibitor widely used for the treatment of advanced Hepatocellular Carcinoma (HCC).A rare but possibly dangerous adverse drug reaction linked to cabozantinib's anti-angiogenic properties is scrotal ulceration. Reduced blood flow and poor tissue repair may contribute to the development of ulcers. About six weeks after starting cabozantinib therapy, a 66-year-old man with advanced hepatocellular carcinoma experienced painful scrotal ulcerations. Clinical examination showed mild erythema and superficial ulcerative lesions with polycyclic boundaries around the scrotum, but no signs of necrotising fasciitis or infection. The lesions completely healed once cabozantinib was stopped, and the patient was treated conservatively with supportive therapy and local wound care. This case report highlights early recognition of cabozantinib-induced genital ulceration and the role of prompt drug withdrawal in management.